O ensino de função polinomial do 1º grau por meio do enfoque ciência, tecnologia e sociedade (CTS) e a contribuição interdisciplinar das ciências - Balbinot, Catia (2023)
One of the difficulties highlighted in learning Mathematics is the lack of contextualization of disciplinary content. In this sense, Critical Mathematics Education (CME) and the Science, Technology and Society (CTS) approach suggest approaches to the context as a way to give meaning to what is taught, enabling relevant learning not only of the disciplinary content, but also to develop citizenship, a fundamental parameter in both. In this sense, the present research aimed to address the content of the first degree polynomial function in a contextualized and interdisciplinary way with the area of ​​Science, more specifically with Chemistry, in order to answer the question raised for the research: "What are the contributions that can emerge in the development of a didactic sequence, supported by the CTS approach, to approach the content of 1st degree polynomial function?" To this end, the educational product developed consisted of a didactic sequence (SD) structured in the methodology of the three pedagogical moments and with the theme "Food Analysis". In addition to the 1st degree polynomial function, concepts that emerge from the topic, such as proportionality, percentage, graphs and, in the area of ​​Science, solutions, concentration units, dilution, among others, constituted the SD. The research was qualitative in nature and the collection instruments were the research teacher's logbook and the evaluation activities proposed to the students. Throughout the development of the work, it was found that the students had a lot of difficulty in the content covered, requiring assistance from the teacher to start carrying out the activities, demonstrating little autonomy in transferring knowledge to other situations, although in the elaboration and use of the polynomial function 1st degree itself, the results were good. For teaching action, the possibility of treating content in an interdisciplinary and contextualized way, focusing on CTS, the profile of the sequence, opened another perspective to act in the classroom in a more convenient way, in order to verify that the recurring questions from students regarding the "applicability" of studying mathematical content, did not present themselves during the DS, signaling that they were perceiving Mathematics from another perspective. It can be seen that SD provided students with a closer look at information that is available to citizens, but which often goes unnoticed; greater involvement in the educational process; the perception of the importance of Mathematics in other areas of knowledge. The educational product resulting from this research is available on the EduCapes website, at the following address.